2015
DOI: 10.3892/or.2015.4535
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid enhances bystander effect of suicide gene therapy in the treatment of breast cancer

Abstract: All-trans retinoic acid (ATRA) has been shown to enhance the expression of connexin 43 (Cx43) and the bystander effect (BSE) in suicide gene therapy. These in turn improve effects of suicide gene therapies for several tumor types. However, whether ATRA can improve BSE remains unclear in suicide gene therapy for breast cancer. In the present study, MCF-7, human breast cancer cells were treated with ATRA in combination with a VEGFP-TK/CD gene suicide system developed by our group. We found that this combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In vivo studies also suggested gap junctions promoted the bystander effect and enhanced ganciclovir therapy 206 . A number of articles substantiated the role of GJIC in the bystander effect 207-211 , including very recent studies in breast cancer 212 , although some studies reported little or no effect 213 . Conversely, it was proposed 214 that HSV-TK transduced cells could be significantly protected from cell death by neighbouring cells via GJIC, possibly through the dilution of ganciclovir (or activated ganciclovir) or by the sharing of survival signals (the so-called “Good Samaritan effect”).…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…In vivo studies also suggested gap junctions promoted the bystander effect and enhanced ganciclovir therapy 206 . A number of articles substantiated the role of GJIC in the bystander effect 207-211 , including very recent studies in breast cancer 212 , although some studies reported little or no effect 213 . Conversely, it was proposed 214 that HSV-TK transduced cells could be significantly protected from cell death by neighbouring cells via GJIC, possibly through the dilution of ganciclovir (or activated ganciclovir) or by the sharing of survival signals (the so-called “Good Samaritan effect”).…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…It is possible that one explanation for these discrepancies is the GJ-mediated transmission of the 'death signal' from apoptotic cells to neighboring viable cells. This strategy, which is followed in GJIC-based therapies, depends on the so-called 'bystander effect' (BE) (43,44). The BE, a mechanism where a cytotoxic signal is transferred from targeted cells to neighboring cells, has been considered as an important therapeutic method (45).…”
Section: A B Discussionmentioning
confidence: 99%
“…therapeutic potential in breast cancer, colorectal cancer, and gastric cancer (39)(40)(41). However, little research exists investigating the relationship between ATRA and NPC.…”
Section: Ra Is a Metabolic Intermediate Of Vitamin A And Atramentioning
confidence: 99%